MARKET INVESTING DESIRE ON SHARIA CAPITAL MARKET: REASON DISCOVERY ON LHOKSEUMAWE COMMUNITY - khairisma, Khairisma; Surya, Nada; Sari, Cut Putri Mellita; Yoesoef, Yoesrizal Muhammad (Fakultas Ekonomi dan Bisnis Islam, 2022)
MARKET INVESTING DESIRE ON SHARIA CAPITAL MARKET Abstract Purpose: This study aims to explore the influence of comprehension and capital, mediated by socialization, on the residents' interest in investing in the Islamic Capital Market in Lhokseumawe. Design/methodology/approach: The research employs a quantitative approach utilizing the SmartPLS application. A questionnaire is used as the measuring instrument, collecting primary and secondary data from a sample population of 130 individuals. Hypothesis testing is conducted to assess the impact of comprehension, capital, and socialization on public interest in Sharia capital market investment. Findings: The results indicate that comprehension, capital, and socialization significantly and positively affect public interest in investing in the Sharia capital market. Socialization, as an intervening variable, also exhibits a positive and significant impact on the community's interest in Islamic capital market investment. Research limitations/implications: The study is confined to the Lhokseumawe community and may not be universally applicable. Additionally, other factors beyond comprehension, capital, and socialization may influence investment decisions. Further research could explore these factors and broaden the scope of the study. Practical implications: Understanding the positive impact of comprehension, capital, and socialization on investment interest suggests that educational initiatives and targeted socialization efforts can enhance community participation in the Sharia capital market. Policymakers and financial institutions can use these findings to develop strategies to promote Islamic capital market investments. Keywords: comprehension; capital; socialization; interest; Sharia capital market KEINGINAN BERINVESTASI DI PASAR MODAL SYARIAH Abstrak Tujuan: Penelitian ini bertujuan untuk mengeksplorasi pengaruh pemahaman dan permodalan yang dimediasi dengan sosialisasi terhadap minat warga untuk berinvestasi di Pasar Modal Syariah di Lhokseumawe. Desain / metodologi / pendekatan: Penelitian ini menggunakan pendekatan kuantitatif menggunakan aplikasi SmartPLS. Kuesioner digunakan sebagai alat ukur, mengumpulkan data primer dan sekunder dari populasi sampel 130 individu. Pengujian hipotesis dilakukan untuk menilai dampak pemahaman, permodalan, dan sosialisasi terhadap minat masyarakat terhadap investasi pasar modal syariah. Kesimpulan: Hasil penelitian menunjukkan bahwa pemahaman, permodalan, dan sosialisasi berpengaruh signifikan dan positif terhadap minat masyarakat untuk berinvestasi di pasar modal syariah. Sosialisasi, sebagai variabel intervening, juga menunjukkan dampak positif dan signifikan terhadap minat masyarakat terhadap investasi pasar modal syariah. Keterbatasan / implikasi penelitian: Penelitian ini terbatas pada komunitas Lhokseumawe dan mungkin tidak dapat diterapkan secara universal. Selain itu, faktor-faktor lain di luar pemahaman, modal, dan sosialisasi dapat mempengaruhi keputusan investasi. Penelitian lebih lanjut dapat mengeksplorasi faktor-faktor ini dan memperluas ruang lingkup penelitian. Implikasi praktis: Memahami dampak positif pemahaman, permodalan, dan sosialisasi terhadap minat investasi menunjukkan bahwa inisiatif edukasi dan upaya sosialisasi yang tepat sasaran dapat meningkatkan partisipasi masyarakat di pasar modal syariah. Pembuat kebijakan dan lembaga keuangan dapat menggunakan temuan ini untuk mengembangkan strategi untuk mempromosikan investasi pasar modal Islam. Kata kunci: pemahaman; modal; sosialisasi; minat; Pasar modal syariah